Relationship between Age and Improvement of Nutritional Status of Stunting Children - Ria Setia Sari; Febi Ratnasari; Yuni Susikowati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aim: to find out the relationship between stunting children's age and improvement in stunting children's nutritional status Methods: This type of research is a descriptive correlational study with a cross sectional approach and uses the total sampling method with 45 respondents. Collecting data using a questionnaire that includes the age of the child, and improvement of nutritional status. Data analysis using chi-square Results: children aged 1-15 months experienced an improvement in nutrition 37% while the same nutritional status was 78%, children aged 16-30 months experienced an improvement in nutritional status 13.3% while those who did not experienced nutritional improvement were 86.7%, aged 46¬- 60 months as much as 50% and did not experience an improvement in nutrition as much as 50%. After the Ch-Square test was carried out with a P-Value of 0.022 that there was no significant relationship between stunting children's age and improvement in stunting children's nutritional status. Conclusions: the improvement of nutritional status in stunted children is not related to the child's age. Other studies on enhancing balanced nutrition could be conducted by other researchers.